The Wonders of Norwegian Wool. Issue 1 (1st April 2013) - Hebrok, Marie; Klepp, Ingun G.
This article draws from research undertaken as part of the Valuing Norwegian Wool project. Here, we will discuss the Norwegianess of Norwegian wool as found and used in Norwegian wardrobes following a wardrobe studies methodology. As a method, the wardrobe study aims to consider the materiality of garments in clothes research outside of but in addition to more usual studies of dress. Analysing the materiality of objects in connection with the social and cultural aspects of clothing facilitates a greater knowledge of the relations between materiality and practice (object and wear). This article addresses the fundamental questions and responses arising from this project: What constitutes Norwegian wool in the minds of Norwegians? How are material, cultural and social aspects of wool co-produced, and how do they relate to each other?